Interlocutory decision declining competence for appeal due to interlocutory appeal: interpretative analysis of art. 1.015 of the Code of Civil Procedure (Research, Society and Development, 2021)
This article deals with the appeal of interlocutory decisions expressed in the Code of Civil Procedure, which now provides for hypotheses of definitive interlocutory decisions on merits, provisional interlocutory decisions on merits and interlocutory decisions. The problematization is found in the initial interpretation of taxativity of Art. 1.015 of the CPC, which provides for the appeal by an Interlocutory Appeal of the interlocutory decisions expressed and those that would not be expressed in the list of the referred article should be raised in a preliminary appeal, being appropriate, for purposes of avoiding the preclusion, the protest, in Art. 278, CPC/2015 or the writ of mandamus. However, recently the Superior Court of Justice understood that the interlocutory appeal against an interlocutory decision that judges a matter of incompetence is appropriate, given the then mitigated interpretation of Art. 1.015 of CPC/2015. For the argumentative construct, deductive methodology is used in the analysis of doctrine, jurisprudence and legislation relevant to the matter.